Mesenchymal stromal cells induce epithelial-to-mesenchymal transition in human colorectal cancer cells through the expression of surface-bound TGF-β - Mele, Valentina (Int J Cancer, 2014)
Mesenchymal stem/stromal cells (MSC) are multipotent precursors endowed with the ability to home to primary and metastatic tumor sites, where they can integrate into the tumor-associated stroma. However, molecular mechanisms and outcome of their interaction with cancer cells have not been fully clarified. In this study, we investigated the effects mediated by bone marrow-derived MSC on human colorectal cancer (CRC) cells in vitro and in vivo. We found that MSC triggered epithelial-to-mesenchymal transition (EMT) in tumor cells in vitro, as indicated by upregulation of EMT-related genes, downregulation of E-cadherin and acquisition of mesenchymal morphology. These effects required cell-to-cell contact and were mediated by surface-bound TGF-β newly expressed on MSC upon coculture with tumor cells. In vivo tumor masses formed by MSC-conditioned CRC cells were larger and characterized by higher vessel density, decreased E-cadherin expression and increased expression of mesenchymal markers. Furthermore, MSC-conditioned tumor cells displayed increased invasiveness in vitro and enhanced capacity to invade peripheral tissues in vivo. Thus, by promoting EMT-related phenomena, MSC appear to favor the acquisition of an aggressive phenotype by CRC cells.